DIMENSIONALITY AND GEOELECTRICAL STRIKE OF MAGNETOTELLURIC DATA USING TENSOR IMPEDANCE IN â€œX-AREAâ€ EAST NUSA TENGGARA, INDONESIA - Heidar, Ismail; Yatini, Y; Asep, Sugianto (Indonesian Physical Review, 2022)
Geothermal exploration was conducted using the magnetotelluric method in â€œX-areaâ€ East Nusa Tenggara, Indonesia, to obtain the potential area and subsurface structure information. Dimensionality analysis and rotation by tensor impedance were conducted to determine the data character and regional geoelectrical strike direction of the 9-point measurement. Skew and polar diagrams were produced to estimate dimensionality inversion and azimuth rotating MT data as geoelectrical strike research areas. The result shows that the domination of skews greater than 0.3 indicates 1-D and 2-D data character. The data was validated by polar diagram analysis at 10-2 Hz to 103 Hz frequency to find 2-D characters and 2D modeling. The geoelectrical strike analysis obtained MT data rotation shows the research area with regional strike N 107Â° E as an azimuth for rotating nine sitesâ€™ MT data. The result of modeling by data analysis shows no ambiguity model, lowest RMS grade, and matches with the geological condition of the research area.